Jurnal Vokasi ANALISIS SISTEM INFORMASI ADMINISTRASI UNTUK PENINGKATAN DAYA DUKUNG BAGI KINERJA KARYAWAN: Bisnis Digital - Rizka Azkiya Megawati; Yanuar Aziz Reza Dwiyan (Politeknik Bisnis Mayasari, 2022)
Information system is something that is very important for the Company, because it is a necessity that can increase the carrying capacity of employee performance. The purpose of this study was to determine and analyze how much the level of utilization of administrative information systems to increase carrying capacity for the employess performance of Politeknik Bisnis Mayasari. This study uses a qualitative method, with data collection techniques used are interviews and observations. Based on the results of the study indicate that the level of utilization of Information Systems has not been used effectively at the Politeknik Bisnis Mayasari (POLBIM). In addition, the addition of quantity and quality of Human Resources is also needed to assist the performance of employees. Therefore, it is necessary to increase theutilization of Information Systems, which are expected to be able to perform and produce the required information easily, quickly, safely, and accurately, in order to increase the carrying capacity of employee performance.